2021
DOI: 10.3390/plants10061216
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Ascophyllum nodosum Extract on the Nutraceutical Antioxidant Potential of Vigna radiata Sprout under Salt Stress

Abstract: Mung bean (Vigna radiata L.) sprout is a popular fresh vegetable, tasty and high in antioxidants. To increase yield and quality after the occurrence of both abiotic and biotic stresses, the application of seaweed extracts is of great importance. Hence, this study was conducted to determine the effect of Ascophyllum nodosum extract (ANE) in the presence of salt on the antioxidant potential of V. radiata sprouts. Different concentrations of ANE viz. 0.00, 0.01, 0.05, 0.10, and 0.50% and NaCl 0, 25, 50, 75, and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 90 publications
(106 reference statements)
1
4
0
Order By: Relevance
“…Similar behavior has been reported for other plant species such as Cynara scolymus L. [ 49 ], and Verbena officinallis L. [ 50 ]. A concentration of 100 mM NaCl combined with the use of Ascophyllum nodosum led to an increased flavonoid concentration in Vigna radiata L. [ 51 ], while 150 mM had the same stimulating effect for Trigonella foenum-graecum L. [ 52 ], confirming the results presented in this study.…”
Section: Discussionsupporting
confidence: 84%
“…Similar behavior has been reported for other plant species such as Cynara scolymus L. [ 49 ], and Verbena officinallis L. [ 50 ]. A concentration of 100 mM NaCl combined with the use of Ascophyllum nodosum led to an increased flavonoid concentration in Vigna radiata L. [ 51 ], while 150 mM had the same stimulating effect for Trigonella foenum-graecum L. [ 52 ], confirming the results presented in this study.…”
Section: Discussionsupporting
confidence: 84%
“…An increase in chlorophyll 'a', chlorophyll 'b', total chlorophyll, and carotenoids in A. esculentus by Rosenvigea intricate [46] and in V. mungo by U. reticulate [8,23] was also observed. The application of A. nodosum was also previously reported to enhance the chlorophyll content in the leaves of Solanum lycopersicum, Hordeum vulgare, Phaseolus vulgaris, Zea mays, V. radiata, and Triticum aestivum [3,47]. Overall, ANE supplied through roots showed better results compared to foliar application of ANE.…”
Section: Discussionmentioning
confidence: 75%
“…(2019) showed that TPC and TFC increased during germination. Previous studies reported the same positive effect by applying seaweed extract as an elicitor in seeds and crops of legumes (Rathore et al., 2009; Fan et al., 2011; Kocira et al ., 2018a; Kumari et al., 2021), but not in peanut. It was also reported that the polysaccharides present in Ulva lactuca extract contributed to the promotion of phenolic metabolism as evidenced by increased PAL activity and higher TPC and lignin content in olive (Ben Salah et al., 2018), sweet pepper and tomato seedlings (Ali et al., 2021).…”
Section: Discussionmentioning
confidence: 98%
“…The antioxidant capacity may be influenced by other components that could affect metabolic functions. Other studies have linked anthocyanins, antioxidant amino acids and bioactive peptides to the antioxidant activity of legume sprouts (León‐López et al., 2020; Kumari et al., 2021). It is likely that different antioxidant compounds may act synergistically to lead to significant antioxidant activity after elicitor treatment (Zhang et al., 2020; Chung et al., 2021; Zhu et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation